Untargeted accurate identification of highly pathogenic bacteria directly from blood culture flasks - Erwin M. Berendsen; Evgeni Levin; René Braakman; Andrei Prodan; Hans C. van Leeuwen; Armand Paauw (Elsevier, 2020)
To improve the preparedness against exposure to highly pathogenic bacteria and to anticipate the wide variety of bacteria that can cause bloodstream infections (BSIs), a safe, unbiased and highly accurate identification method was developed. Our liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based method can identify highly pathogenic bacteria, their near-neighbors and bacteria that are common causes of BSIs directly from positive blood culture flasks. The developed Peptide-Based Microbe Detection Engine (http://proteome2pathogen.com) relies on a two-step workflow: a genus-level search followed by a species-level search. This strategy enables the rapid identification of microorganisms based on the analyzed proteome. This method was successfully used to identify strains of Bacillus anthracis, Brucella abortus, Brucella melitensis, Brucella suis, Burkholderia pseudomallei, Burkholderia mallei, Francisella tularensis, Yersinia pestis and closely related species from simulated blood culture flasks. This newly developed LC-MS/MS method is a safe and rapid method for accurately identifying bacteria directly from positive blood culture flasks.